2018
DOI: 10.33407/itlt.v67i5.2307
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Professional Competencies of the Future Teachers by Means of a Computer-Based Methodology: Investigational Approach

Abstract: The article validates feasibility of the investigational research of the problem of formation of the future teachers’ professional competencies by means of a computer-based methodology; it determines the author’s approach to the interpretation of the essence of the computer-based methodology for the formation of professional competencies of the future teachers; it specifies the structural components of the computer-based methodology of formation of professional competencies of the future teachers: goals (objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Next, the category of each software was defined in the workshop since a previous taxonomy for classification was not found. Although some classifications have been published (Bobryts'ka and Prots'ka, 2018), there were not suitable for this case study.…”
Section: Resultsmentioning
confidence: 99%
“…Next, the category of each software was defined in the workshop since a previous taxonomy for classification was not found. Although some classifications have been published (Bobryts'ka and Prots'ka, 2018), there were not suitable for this case study.…”
Section: Resultsmentioning
confidence: 99%
“…The literature review found an extensive body of research revealing the use of technology in educational settings. The relevant and credible works show that there is the relationship between the use of information communication technology (ICT) and students' academic performance, educational self-efficacy determined by the ability to navigate in the flow of information, to acquire new knowledge, to selfdevelop professionally (Bobrytska, 2015;Bobrytska & Protska, 2017;Bobrytska & Protska, 2018;Chkhalo, n.d.;Saxena, 2017;Balali, Ahmadi, Tabatabaei & Hassani, 2018;Basri, Alandejani & Almadani, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%